Comparison of start-up strategies and process performance during semi-continuous anaerobic digestion of sugarcane filter cake co-digested with bagasse. (February 2016) - Janke, Leandro; Leite, Athaydes F.; Nikolausz, Marcell; Radetski, Claudemir M.; Nelles, Michael; Stinner, Walter
Highlights: Different start-up strategies during AD of filter cake and bagasse were tested. Fresh cattle manure needed 20 days of acclimation to be proper used as inoculum. AD of filter cake resulted in higher biogas yield than co-digestion with bagasse. Co-digestion with bagasse would produce +58% biogas in a large-scale application. Abstract: The anaerobic digestion of sugarcane filter cake and the option of co-digestion with bagasse were investigated in a semi-continuous feeding regime to assess the main parameters used for large-scale process designing. Moreover, fresh cattle manure was considered as alternative inoculum for the start-up of biogas reactors in cases where digestate from a biogas plant would not be available in remote rural areas. Experiments were carried out in 6 lab-scale semi-continuous stirred-tank reactors at mesophilic conditions (38 ± 1 °C) while the main anaerobic digestion process parameters monitored. Fresh cattle manure demonstrated to be appropriate for the start-up process. However, an acclimation period was required due to the high initial volatile fatty acids concentration (8.5 g L −1 ). Regardless the mono-digestion of filter cake presented 50% higher biogas yield (480 mL gVS −1 ) than co-digestion with bagasse (320 mL gVS −1 ) during steady state conditions. A large-scale co-digestion system would produce 58% more biogas (1008 m 3 h −1 ) than mono-digestion of filter cake (634 m 3 h −1 ) due to its higher biomass availability for biogas conversion. Considering that the biogas production rate was the technical parameter that displayed the most relevant differences between the analyzed substrate options (0.99–1.45 m 3 biogas m 3 d −1 ). The decision of which substrate option should be implemented in practice would be mainly driven by the available construction techniques, since economically efficient tanks could compensate the lower biogas production rate of co-digestion option.